Cannabis Inflorescence Yield and Cannabinoid Concentration Are Not Increased With Exposure to Short-Wavelength Ultraviolet-B Radiation - Rodriguez-Morrison, Victoria; Llewellyn, David; Zheng, Youbin (Frontiers in Plant Science, 2021)
Before ultraviolet (UV) radiation can be used as a horticultural management tool in commercial Cannabis sativa (cannabis) production, the effects of UV on cannabis should be vetted scientifically. In this study we investigated the effects of UV exposure level on photosynthesis, growth, inflorescence yield, and secondary metabolite composition of two indoor-grown cannabis cultivars: ‘Low Tide’ (LT) and ‘Breaking Wave’ (BW). After growing vegetatively for 2 weeks under a canopy-level photosynthetic photon flux density (PPFD) of ≈225 μmol⋅m–2⋅s–1 in an 18-h light/6-h dark photoperiod, plants were grown for 9 weeks in a 12-h light/12-h dark “flowering” photoperiod under a canopy-level PPFD of ≈400 μmol⋅m–2⋅s–1. Supplemental UV radiation was provided daily for 3.5 h at UV photon flux densities ranging from 0.01 to 0.8 μmol⋅m–2⋅s–1 provided by light-emitting diodes (LEDs) with a peak wavelength of 287 nm (i.e., biologically-effective UV doses of 0.16 to 13 kJ⋅m–2⋅d–1). The severity of UV-induced morphology (e.g., whole-plant size and leaf size reductions, leaf malformations, and stigma browning) and physiology (e.g., reduced leaf photosynthetic rate and reduced Fv/Fm) symptoms intensified as UV exposure level increased. While the proportion of the total dry inflorescence yield that was derived from apical tissues decreased in both cultivars with increasing UV exposure level, total dry inflorescence yield only decreased in LT. The total equivalent Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) concentrations also decreased in LT inflorescences with increasing UV exposure level. While the total terpene content in inflorescences decreased with increasing UV exposure level in both cultivars, the relative concentrations of individual terpenes varied by cultivar. The present study suggests that using UV radiation as a production tool did not lead to any commercially relevant benefits to cannabis yield or inflorescence secondary metabolite composition.